PIR with P-Cache: A New Private Information Retrieval Protocol With Improved Performance - Md. Latiful Hoque, Dr. Abu Sayed; Hossain, Gahangir (Malaysian Journal of Computer Science, 2008)
The increasing model of e-commerce infrastructure opens the door for secure transaction of information over the Net, keeping some records private as users’ choice within a few seconds. A client, while frequently retrieving his records, seldom wishes to hide the identity of the records to the database server. Private Information Retrieval (PIR) protocols allow users to retrieve information from a database while keeping their query private. Existing protocols have pros and cons in terms of communication and computational complexity. In some PIRs the computational complexity is reduced to O(1), and optimal, but still holds the high communication complexity O(Ns) as there is a huge amount of communication needed to satisfy the query. In our research a new PIR, namely PIR with P-cache, is introduced, based on the concept of database caching technology. In an average case, whenever a client requests a query in the system, there is a high probability to satisfy it from the P-cache instead of accessing the main database server that contains a huge amount of records. Our protocol outperforms the existing protocols in terms of both communication and computational complexity for queries supporting from P-cache and hence an improved performance.